(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
Hyperglycemia is the major risk factor for atherosclerosis and cardiovascular diseases, which is associated with several cardio-metabolic risk factors such as diabetes, hypercholesterolemia and high blood pressure. The antihyperglycemic properties of the herbal mixture (HM) from Salvia officinalis L., Calendula officinalis Linn., Glycyrrhizae radix L. and Echinacea purpurea L. in rabbits with hyperglycemia induced by immobilization stress have been evaluated, hypoglycemic activity, improved lipid profile and body weight, to restore liver and muscle glycogen levels by HM aqueous extract were revealed.